Prospectively assessed hypothalamic-pituitary dysfunction after proton therapy in adults with head and neck, skull base and brain tumors - Jordan Bouter; Nathan Azemar; Anthony Vela; Pauline Dutheil; Paul Lesueur; Dinu Stefan; Yves Reznik; Juliette Thariat (Scientific Reports)
Abstract Radiotherapy is advocated for many brain and head and neck tumors close to the pituitary gland. Pituitary hormones govern many vital functions but data of standardized monitoring for deficiencies after irradiation are lacking. We prospectively assessed the latency and frequency of hypothalamo-pituitary radiation dose-effects in patients undergoing proton therapy or mixed photon /proton beams for CNS, skull base and head and neck tumors. Radiation oncologists prospectively were asked to monitor endocrine functions based on a standardized protocol complying with international recommendations at 6, 12 months and yearly during follow-up. Patient, tumor and treatment characteristics were collected. Seventy patients (women 70%, median age 60.1 years) had undergone endocrine monitoring with a median follow-up of 20.7 (12.8–29.5) months. Thirty percent of patients had at least one pituitary deficiency before radiotherapy. Median mean dose to the pituitary gland and hypothalamus were respectively 52.0 (50.4–53.9) Gy and 24.7 (16.8–39.2) Gy. Of these patients with heavily exposed on their pituitary gland, skull base meningiomas (47.1%) and pituitary adenomas were the most represented (28.7%). Twenty-six (37.1%) patients experienced a new pituitary deficiency after a median time of 14.1 [IQR 10.3–23.6] months. Lactotroph and gonadotroph axis deficiencies occurred in 36% and 23.2% of the patients after 13.5 and 24.5 months, respectively. GH deficiency occurred in 9.7% patients after 27.1 months. TSH and ACTH axes occurred in 7.8% and 6.3% of patients after 21.8 and 19.0 months. On univariate analysis, only BMI < 25 was significantly associated with a shorter time to new deficiency onset. In this selected population of patients receiving over 50 Gy RBE to the pituitary gland, patients frequently developed at least one new pituitary deficiency within 2 years. As hormonal deficiencies are frequent after surgery and radiotherapy have functional and quality-of-life consequences and can be substituted medically, baseline and routine annual monitoring of every axis were performed. Educational programs for patients and physicians toward more systematic monitoring in patients, including those receiving < 30 Gy could serve to analyze radiation dose-effects and better predict individual endocrine normal tissue complication probabilities (NTCP).